The Association Between Experimentally Induced Stress, Performance Monitoring, and Response Inhibition: An Event-Related Potential (ERP) Analysis - Rodeback, Rebekah E.; Hedges-Muncy, Ariana; Hunt, Isaac J.; Carbine, Kaylie A.; Steffen, Patrick R.; Larson, Michael J. (Frontiers in Human Neuroscience, 2020)
Psychological stress is increasingly associated with alterations in performance and affect. Yet, the relationship between experimentally-induced psychological stress and neural indices of performance monitoring and error processing, as well as response inhibition, are unclear. Using scalp-recorded event-related potentials (ERP), we tested the relationship between experimental stress, using the Trier Social Stress Test (TSST), and the error related negativity (ERN), error positivity (Pe), and N2 ERP components. A final sample of 71 undergraduate students were randomly assigned to go through the TSST (n = 36; 18 female) or a brief mindfulness relaxation exercise (n = 35; 16 female) immediately followed by a go/no-go task while electroencephalogram (EEG) data were collected. Salivary cortisol, heart rate, and blood pressure confirmed increased physiological stress in the TSST group relative to control. Reaction times, accuracy, and post-error slowing did not differ by stress group. Two-group (TSST, control) by 2-trial type (correct, incorrect for ERN/Pe; go correct, no-go correct for N2) repeated measures ANOVAs for the ERN, Pe, and N2 showed the expected main effects of trial type; neither the ERN nor the N2 ERP components showed interactions with the stress manipulation. In contrast, the Pe component showed a significant Group by Trial interaction, with reduced Pe amplitude following the stress condition relative to control. Pe amplitude did not, however, correlate with cortisol reactivity. Findings suggest a reduction in Pe amplitude following experimental stress that may be associated with reduced error awareness or attention to errors following the TSST. Given the variability in the extant literature on the relationship between experimentally-induced stress and neurophysiological reflections of performance monitoring, we provide another point of data and conclude that better understanding of moderating variables is needed followed by high-powered replication studies to get at the nuance that is not yet understood in the relationship between induced stress and performance monitoring/response inhibition processes.